ICT Usage Amongst Lecturers and Its Impact Towards Learning Process Quality - Lubis, Andre Hasudungan; Syed Idrus, Syed Zulkarnain; Sarji, Asiah (Universiti Kebangsaan Malaysia Press, 2018)
The use of ICT in education has caused substantial changes in learning and brought many benefits to higher learning institutions.However, the development of ICT in the institution of higher education in Indonesia is a minus value compared to other Southeast Asia countries (e.g., Singapore and Malaysia).This is due to several factors which are the lack of knowledge and lack of motivation, especially in Medan, North Sumatera.Medan as the fourth largest city in Indonesia has a low penetration of ICT utilization compared to the other cities which is smaller than it is.Previous studies have found that there is a positive relationship between variables, which are motivation towards ICT usage, knowledge level towards ICT usage, and ICT usage towards learning process quality.This paper addresses the issue by demonstrating a method of study to identify the impact of ICT usage towards learning process quality by lecturers in Medan, Indonesia.As a result, the application of the quantitative research design and data collection through survey questionnaire was considered as the most appropriate method to receive the outcome of the study. Statistical techniques which are the descriptive statistical analysis and regression analysis methods proposed as the means to analyze the data.